THE IRISH FACTOR IN THE US POLITICS DURING 1968 – 1998 - Oleksandr Komarenko; Oleh Prelovskyi (Американська історія і політика)
The article is meant to discuss the Irish diaspora in the United States of America, and its influence on US politics during the period from 1968 to 1998. The study aims to analyse the diaspora influence on the US foreign policy regarding the Northern Irish issue, the factors of formation and changes in the lives of immigrants, and their perspective towards the United Kingdom and the Republic of Ireland. The chronological period is determined by the duration of the Troubles, that is the Northern Ireland ethnic conflict.